Program Ecomposter Sebagai Upaya Pengelolaan Sampah Skala Rumah Tangga - Ayu Riana Sari Azwari; Farah Azwadina Umi; Ratna Mulia Wati; Farah Purwandani Shaleha; Fatma Liliansi Nora; Genoveva Adya Rika Elshadai (Jurnal Pengabdian UNDIKMA, 2023)
This community service activity aims to increase community knowledge and skills in managing organic and inorganic waste through ECOMPOSTER (ecobrick and composter) programs. The method of implementing this service used counseling and demonstration methods, including educational activities on waste sorting, training on making ecobrick and compost using the Takakura method, and forming ecomposter cadres. The partners of this service were the people of Wonorejo Village RT. 5 and 6, Satui District, Tanah Bumbu Regency, South Kalimantan Province. The instrument for evaluating this activity used a knowledge questionnaire which was statistically analyzed with a paired T-test, an attitude questionnaire which was statistically analyzed with the Wilcoxon test, and a final program evaluation questionnaire which was analyzed descriptively. The results of this service showed that there were significant differences in knowledge and attitudes before and after the provision of education, indicated by a p value <0.05 (0.0007) in knowledge and a p-value <0.05 (0.0036) in attitude. In addition, from the results of this activity, 15 households used the Takakura method of compost, and 23 households made ecobricks at their homes.